Transparansi Penggunaan Dana Desa Dalam Rangka Meminimalisir Patologi Administrasi - Hamirul, Hamirul - (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
This article aims to find out the realization of the use of Village Funds in the village agreed to unite the Rimbo Ilir sub-district, Tebo Regency, Jambi Province. By using the deskripif method with a qualitative approach. Data collection techniques used were interviews with informants as many as 10 people, then the data was analyzed using Trianggulasi. Research Results The use of Sepakat Bersatu village funds has been implemented in accordance with the existing rules in village financial reporting, namely by utilizing the Sikeudes application system, the implementation of the application was implemented in early 2017 in the use of village funds. planning stage and that which has been realized and pathologies be minimalilize . While efforts were made to overcome these obstacles, namely approaching the community directly or cooperating with the RT head of each RT in the Sepakat Bersatu Village. The second attempt was made by the Sepakat Bersatu village government in overcoming the constraints of a lack of understanding in the SISKEUDES application frontline namely conducting training for village communities and also consulting with the Village Community Empowerment Agency (PMD) Keywords: Realization, ADD, Sepakat Bersatu Village, Tebo.